The effects of caffeine supplementation on strength and muscular endurance in resistance-trained women - Goldstein, E.; Jacobs, P.; Antonio, J.; Whitehurst, M.; Penhollow, T. (The Journal of Strength and Conditioning Research, 2010)
The role of caffeine supplementation in strength and power performance is progressively emerging, but with varied results. Moreover, research that has specifically examined the effects of caffeine in strength and women is limited. To determine the acute effects of caffeine supplementation on strength and muscular endurance in resistance-trained women. In a randomized, double-blind crossover design, fifteen women (mean +/- SD age = 25 +/- 7 yrs; body mass = 64 +/- 8 kg; height = 166 +/- 9 cm) consumed caffeine (6 mg/kg) or placebo (PL) in randomized order, seven days apart. Sixty min following supplementation, participants performed a one-repetition maximum (1RM) barbell bench press test and repetitions to failure at 60% of 1RM. Heart rate, blood pressure (systolic and diastolic), and rating of perceived exertion were assessed at rest, 60 minutes post-consumption, and immediately following completion of repetitions to failure. A one-way ANOVA for repeated measures was used to analyze potential differences between caffeine and placebo conditions. Analysis indicated a significantly greater bench press maximum with caffeine (p <= 0.05) (52.9 +/- 11.1 kg vs. 52.1 +/- 11.7 kg) with no significant differences between conditions in 60% 1RM repetitions (p = 0.81). The only statistically significant differences between conditions in physiological measures was a greater systolic blood pressure immediately following exercise, with caffeine (p < 0.05) (116.8 +/- 5.3 mmHg vs. 112.9 +/- 4.9 mmHg). Our findings indicate that caffeine appears to be effective for improving upper extremity strength in resistance-trained women. A moderate dose of caffeine may be sufficient for enhancing strength performance in resistance-trained women.